Lifestyle medicine intervention in neurodevelopmental disorders. Case Report: Intervención con Medicina del Estilo de Vida en trastornos del neurodesarrollo. Reporte de caso - Velásquez Toro, Jonathan (2021)
Neurodevelopmental disorders are conditions generated by dysfunction or interruption of brain development during childhood. In this group, attention deficit hyperactivity disorder and autism spectrum disorder stand out due to their prevalence and association between them. Studies suggest that these patients, due to their behavioral dysfunctions, develop unhealthy lifestyles, and that, in turn, these same habits could exacerbate these behaviors. We present a case of a 5 year old female with diagnoses of grade 1 autism spectrum disorder and attention deficit hyperactivity disorder, under pharmacological and non-pharmacological treatment without behavioral improvement. A lifestyle medicine approach was carried out with an emphasis on eating patterns, transitioning to a plant based diet, incorporating physical activity and sleep hygiene measures. At four months there is evident improvement in hyperactivity, attention and socialization.